The effect of self-management education on quality of life of clients with coronary heart disease - Cahyaningrat, Divya; Lukmanulhakim, Lukmanulhakim (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
Coronary Heart Disease (CHD) is still the number one cause of death in the world with 17.3 million deaths each year. CHD provides an impact in the form of physical and psycho-emotional symptoms, it will affect the quality of life of the client and self-management is a controlling factor to increase client satisfaction in living life. This study aims to identify the influence of education about self- management on the quality of life of clients with coronary heart disease in the Poly Heart of RSUD Dr. Drajat Prawiranegara Serang. Quasi-experimental research with a one-group design pre-post test. The number of samples is 25 CHD  clients with the method of taking using purposive sampling. Data collection tool to measure the quality of life using the WHOQOL BREF instrument. Univariate analysis is presented in the form of mean, standard deviation, percentage and frequency distribution, while bivariate analysis uses t-dependent test (paired sample t-test). Univariate analysis results obtained mean ± SD of quality of life before being given self-management education 38.52 ± 5.53. While the mean quality of life after being given education was 59.64 ± 3.067. The results of the bivariate analysis obtained the mean ± SD difference of 21.12 ± 6.26 with p value = 0,000. There is an influence of self-management education on quality of life for clients with coronary heart disease. Nursing staff should be able to apply health education to CHD clients as a medium for the development of interventions in the event of decreased quality of life experienced by CHD clients.Pengaruh Edukasi Tentang self Management Terhadap Kualitas Hidup Pasien Dengan Penyakit Jantung KoronerAbstrakPenyakit jantung koroner (PJK) masih menjadi penyebab kematian nomor satu di dunia dengan 17,3 juta kematian setiap tahun nya. PJK memberikan dampak berupa gejala fisik dan psikoemosional, hal tersebut akan mempengaruhi kualitas hidup klien dan self management merupakan faktor pengendali untuk meningkatkan kepuasan klien dalam menjalani hidup. Penelitian ini bertujuan untuk mengidentifikasi adanya pengaruh edukasi tentang self management terhadap kualitas hidup pada klien dengan penyakit jantung koroner di Poli Jantung RSUD dr. Drajat Prawiranegara Serang. Penelitian berjenis quasi eksperiment dengan pre-post test one-group design. Jumlah Sampel sebanyak 25 klien PJK dengan metode pengambilan menggunakan purposive sampling. Alat pengumpulan data untuk mengukur kualitas hidup menggunakan instrumen WHOQOL BREF. Analisis univariat disajikan dalam mean, Standar deviasi, persentasi dan distribusi frekuensi, sementara, analisis bivariat menggunakan uji t-dependent (paired sample t-test). Hasil analisis univariat didapatkan nilai mean(SD) kualitas hidup sebelum diberikan edukasi self management 38,52(5,53). Sementara nilai mean kualitas hidup setelah diberikan edukasi didapatkan 59,64(3,067). Hasil analisis bivariat didapatkan nilai selisih mean(SD) sebesar 21,12(6,26) dengan p vaue=0,001. Ada pengaruh edukasi self management terhadap kualitas hidup pada klien dengan penyakit jantung koroner. Tenaga keperawatan sebaiknya dapat menerapkan edukasi kesehatan kepada klien PJK sebagai media untuk pengembangan intervensi pada kejadian penurunan kualitas hidup yang dialami oleh klien PJK.